2016
DOI: 10.1136/annrheumdis-2016-eular.2475
|View full text |Cite
|
Sign up to set email alerts
|

SAT0401 Two-Years Survival of Golimumab in 400 Patients with Rheumatoid Arthritis, Psoriatic Arthritis, and Axial Spondyloarthritis in Real-Life World

Abstract: BackgroundIt has previously been shown that the survival of anti-TNF drugs was lower in Rheumatoid arthritis (RA) than in other chronic arthritis.ObjectivesThe objective of this study was to investigate the drug retention, as surrogate of effectiveness, of Golimumab (GOL) with axial Spondyloarthritis (AxSpA), Psoriatic arthritis (PsA) and RA. Furthermore, predictors of drug retention were evaluated.MethodsThis is a multicenter prospective observational study of unselected patients with AxSpA, PsA and RA starti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, among the 14 out of 17 possible combinations of measurement time-points and treatment lines, patients with axial SpA exhibited higher persistence than patients with RA or PsA. The fourth study, Santo et al, 29 found that in a mix of biologic-naive and biologic-experienced patients, patients with axial SpA had numerically higher crude persistence than patients with RA and PsA, although the difference was not statistically significant when tested in a semiparametric model controlling for confounders.…”
Section: Resultsmentioning
confidence: 98%
“…However, among the 14 out of 17 possible combinations of measurement time-points and treatment lines, patients with axial SpA exhibited higher persistence than patients with RA or PsA. The fourth study, Santo et al, 29 found that in a mix of biologic-naive and biologic-experienced patients, patients with axial SpA had numerically higher crude persistence than patients with RA and PsA, although the difference was not statistically significant when tested in a semiparametric model controlling for confounders.…”
Section: Resultsmentioning
confidence: 98%